Pengaruh Corporate Governance, Pertumbuhan Penjualan dan Kepemilikan Institusional terhadap Manajemen Pajak - Meiliani, Berliana; Rusdi, Rusdi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study examines the influence of corporate governance, sales growth, and institutional ownership on tax management in Consumer Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during 2019-2023. The research applies a quantitative associative method using secondary data obtained from audited annual reports. A total of 45 firm-year observations were selected through purposive sampling. The data were analyzed using panel data regression with EViews 12. The results show that the number of commissioners, the proportion of independent commissioners, and institutional ownership have a significant positive effect on tax management. Meanwhile, the compensation of the board of commissioners and sales growth have no significant effect. These findings indicate that good corporate governance mechanisms play an essential role in shaping tax management behavior. Strengthening oversight and institutional participation is therefore crucial to ensuring responsible tax practices and enhancing corporate transparency.